FENOMENA DEPRESI DI ERA MODERN DAN SPIRITUALITAS KEBAHAGIAAN: STUDI ATAS PEMIKIRAN JALALUDDIN RUMI DAN BUYA HAMKA - Amalih, Ihwan; Sholehah, Tantriatus (Institut Dirosat Islamiyah Al-Amien Prenduan, 2025)
The phenomenon of depression and the search for happiness has become an increasingly relevant issue in the context of modern life full of social pressures and high expectations. In the midst of the hustle and bustle of modern times, individuals often feel dissatisfied with their lives, even though materialistically much has been achieved. The writing of this article aims to know the reinterpretation of the meaning of happiness from the perspective of Jalal al-Din al-Rumi and Buya Hamka and its correlation with the phenomenon of depression in the modern era and to find out the similarities and differences between the meaning of happiness from the perspective of Jalal al-Din al-Rumi and Buya Hamka. This research is a library research with descriptive and comparative analysis to compare the views of the two figures. Research results show that happiness in the modern era is often associated with materialism and hedonism, which leads to an understanding of happiness as worldly achievements and physical satisfaction, which creates errors in understanding happiness. The phenomenon of depression experienced by modern society is often triggered by dissatisfaction with materials and difficulties in dealing with the pressures of life. The reinterpretation of happiness according to Rumi and Hamka emphasizes that true happiness does not lie in material things alone, but in spiritual pleasures that transcend physical limits. Both agree that ultimate happiness is related to closeness to God and self-control of worldly dependence, but Rumi emphasises the spiritual aspect through love of God and avoiding selfishness, while Hamka emphasises the importance of using reason and wisdom in interpreting the world and material.